GAMBARAN PENGETAHUAN INFORMASI DAN SIKAP IBU BALITA DALAM PEMANFAATAN POSYANDU DI WILAYAH KERJA PUSKESMAS KWANDANG MEDICAL CENTER - Pipin Yunus; Haslinda Damansyah (-, 2021)
Background: Visit posyandu toddlers at 18 existing health centers in 7 working area Kwandang medical center in 2013 average - average only reached 58.0% of the specified target is 65%. This is caused because the average - average level of knowledge, information and attitudes about the toddler's mother posyandu utilization is still low. Objective: Aiming to know how is the knowledge and attitude information in the toddler's mother posyandu utilization. Method: This study is a descriptive survey research approach. Population of 101 respondents. The sampling technique used was simple random sampling. The instrument used was a questionnaire and data analysis techniques using univariate analysis. Results: note that the respondents have knowledge in the utilization category posyandu not know that 59 respondents (58.4%) and category know that 42 respondents (41.6%). Most of the respondents amounted to 61 respondents (60.4%) no information about the health posts and 40 respondents (39.6%) no information. Attitudes of mothers in the neighborhood health center utilization in the category is not well 65 respondents (64.4%) while the rest either category accounted for 36 respondents (35.6%). Conclusion: based on the results obtained that the toddler's mother knowledge in the use of labor in the region posyandu Kwandang medical center health clinic in 2014 are included in the category of mothers do not know that 59 infants (58.4%). Toddler's mother in the utilization of information included in the category posyandu no toddler's mother is 61 (60.4%). The attitude of mothers of infants in a neighborhood health center utilization category not included in either the 65 mothers infants (64.4%).